IMPLEMENTATION OF TURBOCHARGER IN TWO WHEELER (International Journal of Engineering Sciences & Management Research, 2017)
The main purpose of this systeme is to use the wastage exhaust gas to rotate the turbine . This turbine rotates the compressor & this compressor compress atmospheric air at high pressure & then it given to the engine cylinder through inlet manifold & use improve the thermal efficiency of the engine& also carnot efficiency of the engine.